ANALYSIS OF TIKTOK NETIZENS' RECEPTION OF GIMMICK MARKETING IN PRILLY LATUCONSINA'S "OPEN TO WORK" CAMPAIGN FOR SENSODYNE ON THE LINKEDIN PLATFORM - Annisa Putri; Diana Amalia (INJOSEDU: International Journal of Social and Education, 2026)
The advancement of digital marketing strategies has encouraged brands to adopt user-generated content (UGC)-style marketing to create a sense of authenticity through content that resembles users' personal experiences. Although this approach is effective in attracting audience attention, it also has the potential to blur the distinction between personal content and promotional messages, leading to diverse audience interpretations. This study aims to analyze TikTok netizens' reception of the gimmick marketing strategy employed in Prilly Latuconsina's Open to Work campaign for Sensodyne on the LinkedIn platform. The study employed a qualitative approach using a descriptive method. Data were collected through in-depth interviews with five purposively selected informants and analyzed using Stuart Hall's reception analysis theory through the encoding-decoding framework. The findings indicate that the UGC-style marketing strategy successfully established a perception of authenticity during the initial stage, leading most informants to perceive the post as a genuine personal experience. However, after the commercial nature of the campaign was revealed, audience reception shifted. Three informants were categorized within the oppositional reading position, one informant within the negotiated reading position, and one informant within the dominant reading position. Differences in audience reception were influenced by the informants' personal experiences, backgrounds, and emotional proximity to employment-related issues. Furthermore, most informants experienced difficulty associating the campaign narrative with the Sensodyne brand and its products, indicating that the campaign's brand relevance was not fully achieved. These findings suggest that the success of gimmick marketing is determined not only by its ability to generate virality but also by contextual appropriateness, communication transparency, sensitivity to social issues, and the clarity of the relationship between the promotional message and the brand identity.